Pengaruh Inflasi, Sertifikat Wadiah Bank Indonesia, Skor Tukar Rupiah Terhadap Non Performing Financing (Npf) Pada Bank Umum Syariah Tahun 2015-2018 - Windasari, Tasya Feby; Diatmika, I Putu Gede (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine the inflation variable, Bank Indonesia Wadiah Certificates, and the rupiah exchange rate for non performing financing. The population in this study is the Indonesian Islamic Banking Statistics published by the OJK. The sample used in this study is the Indonesian Islamic Banking Statistics published by the OJK in 2015-2018. The research method used in this research is quantitative research methods with secondary data obtained from Indonesian Islamic Banking Statistics from the 2015-2018 period. As for the inflation variable, the bank Indonesia wadiah certificate and the rupiah exchange rate were obtained from Indonesian Economic and Financial Statistics data from Bank Indonesia from the 2015-2018 period. The data were analyzed using several analyzes such as classical assumption test and hypothesis test (multiple linear regression analysis, determination coefficient test, t test) with the help of SPSS. The results of this study indicate that the inflation variable (X1) and the rupiah exchange rate (X3)) has a positive and significant effect on non-performing financing (Y). Meanwhile, the Wadiah Bank Indonesia Certificate (X2) variable has a negative and significant effect on non-performing financing (Y).Â